Gender Differences in Academic Performance of Basic 3 Adhd Pupils Taught Social Studies Using Cross-Age Peer Tutoring in Port Harcourt Metropolis, Rivers State - Jasper Abowei; Florence Ebikienmo (MultiTech Publisher, 2025)
This study investigates gender differences in the academic performance of Basic 3 Attention Deficit Hyperactivity Disorder (ADHD) pupils taught Social Studies using cross-age peer tutoring in Port Harcourt Metropolis, Rivers State. The study employed a quasi-experimental design, comparing the pre-test and post-test scores of male and female ADHD pupils exposed to cross-age peer tutoring. Results revealed that male pupils performed better than their female counterparts at both stages, with a statistically significant difference confirmed by ANCOVA analysis (F = 590.158, p < 0.05). These findings suggest that while cross-age peer tutoring enhances learning outcomes for ADHD pupils, gender disparities persist, potentially influenced by cognitive, social, and environmental factors. The study highlights the effectiveness of peer tutoring in supporting ADHD learners by providing structured interactions that enhance engagement and retention. However, the observed gender gap calls for targeted interventions to improve female pupils’ learning experiences. Recommendations include teachers implementing additional support mechanisms to enhance the learning experiences of female ADHD pupils. This may include tailored instructional materials, differentiated instruction, and mentoring programs.